Smart trust : creating prosperity, energy and joy in a low-trust world - Covey, Stephen M. R.; Link, Greg, 1950-; Merrill, Rebecca R. (New York : Free Press, 2012)
In an ever-challenging world, trust continues to be the most pivotal element needed in successful relationships--from the personal to the political to business. With compelling examples, convincing research, and penetrating insights, the authors teach people how to develop optimal trust relationships.
In an ever-challenging world, trust continues to be the most pivotal element needed in successful relationships--from the personal to the political to business. With compelling examples, convincing research, and penetrating insights, the authors teach people how to develop optimal trust relationships.
Pt. 1. The paradox and the promise. The great paradox ; Blind trust or distrust: which glasses are you wearing? ; The third alternative:'Smart Trust' -- pt. 2. The 5 actions of Smart Trust. Smart Trust action 1: Choose to believe in trust ; Smart Trust action 2: Start with self ; Smart Trust action 3: Declare your intent ... and assume positive intent in others ; Smart Trust action 4: Do what you say you are going to do ; Smart Trust action 5: Lead out in extending trust to others -- pt. 3. What can you do?. Creating your own renaissance of trust.
Includes bibliographical references and index.
Keywords: Business ethics; Trust; Ethics; Leadership -- Moral and ethical aspects; Organizational behavior